Changes in Ocular Perfusion Pressure in Response to Short Term Isometric Exercise in Young Adults (Nigerian Journal of Physiological Sciences, 2021)
Summary: Ocular Perfusion Pressure (OPP) is the pressure difference between the Mean Arterial Pressure (MAP) and the Intra Ocular Pressure (IOP). Decreased OPP could be a major risk factor for glaucoma. The aim is to study the effect of Isometric exercise on OPP in apparently healthy young adults. Forty apparently healthy young adult volunteers comprising 20 males and 20 females in the age group of 18-21 years were selected among MBBS Phase I students of JSS Medical college, JSSU, Mysore. IOP and BP were recorded. Mean arterial pressure (MAP) and OPP were calculated. There was a statistically significant difference (p